'Where "Daddy" and Danger Were': The Portrayal of Children in War Illustrated, 1914–16. (May 2014) - R, J
Abstract : This paper examines the representation of children in the popular British First World War publication, War Illustrated . Images of children occur within several contexts, linked to dominant contemporary propaganda discourses. These include concepts of national mobilisation within total war, qualities of sacrifice, endurance and patriotism and the demonisation of German tactics of 'frightfulness' (i.e. atrocities inflicted upon civilians). The magazine's visual representations of children, in photographs and illustrations by war artists, mobilise them as resources in propaganda, to support the prosecution of the war through the propagation of patriotic principles and the vilification of the enemy. Images of women and children in Europe reinforced contemporary propaganda discourses (such as the pervasive 'rape of Belgium' narrative). By comparison, children in Britain became symbols of the ideals of family and country which British soldiers had to defend. However, beyond their representation as victims of the war, children were also represented as participants in the conflict, in some cases assuming the status of combatants comparable to adults. This adaptation of children's roles was matched and eventually overtaken in the magazine's images by the reporting of the transformation of the status of women, and their burgeoning contribution to the war effort as the conflict continued.